Modeling a global supply chain for a two-wheeler manufacturer - Dubey, Rameshwar (2010)
The research paper explores how simulation modeling helps to design a global supply chain by minimizing Forrester effects. The simulation results show through a case study how one of the leading two-wheeler manufacturing companies in India could improve its innovative product forecasting and reduce the risk from currency fluctuations.